2017
DOI: 10.1074/jbc.m117.811547
|View full text |Cite
|
Sign up to set email alerts
|

Loss of hepatic AMP-activated protein kinase impedes the rate of glycogenolysis but not gluconeogenic fluxes in exercising mice

Abstract: Pathologies including diabetes and conditions such as exercise place an unusual demand on liver energy metabolism, and this demand induces a state of energy discharge. Hepatic AMP-activated protein kinase (AMPK) has been proposed to inhibit anabolic processes such as gluconeogenesis in response to cellular energy stress. However, both AMPK activation and glucose release from the liver are increased during exercise. Here, we sought to test the role of hepatic AMPK in the regulation of glucose-producing and citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 83 publications
(114 reference statements)
6
76
2
Order By: Relevance
“…Recently, AMPK was shown to phosphorylate and activate PDE4B, and subsequently inhibit glucagon‐stimulated increases in hepatic cAMP (Johanns et al, ). AMPK has also been reported to regulate liver glycogenolysis during exercise (Andreelli et al, ; Hughey et al, ; Steinberg et al, ). However, in the current study neither exercise training nor acute treatment with epinephrine impacted liver AMPK signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, AMPK was shown to phosphorylate and activate PDE4B, and subsequently inhibit glucagon‐stimulated increases in hepatic cAMP (Johanns et al, ). AMPK has also been reported to regulate liver glycogenolysis during exercise (Andreelli et al, ; Hughey et al, ; Steinberg et al, ). However, in the current study neither exercise training nor acute treatment with epinephrine impacted liver AMPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AMPK was shown to phosphorylate and activate PDE4B, and subsequently inhibit glucagon-stimulated increases in hepatic cAMP (Johanns et al, 2016). AMPK has also been reported to regulate liver glycogenolysis during exercise (Andreelli et al, 2006;Hughey et al, 2017;Steinberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies using nonspecific AMPK activators such as AICAR 143,144 indicated that AMPK repressed key gluconeogenic genes such as those encoding phosphoenolpyruvate kinase (PEPCK) and glucose-6-phosphatase (G6Pase), both of which have been shown to contribute to aberrant hepatic glucose production in metabolic disorders 145 . However, AMPK becomes activated in the liver during exercise, an effect associated with increased, not lower, hepatic glucose output 146 . Studies using a combination of genetic mouse models lacking AMPK and direct AMPK activators (see below) have found that acute AMPK activation does not inhibit hepatic gluconeogenesis and that previous observations using nonspecific activators such as AICAR or metformin may have been related to the inhibition of adenylyl cyclase or alterations in mitochondrial redox status 25,83,147,148 .…”
Section: [H1] Regulation Of Ampk Activitymentioning
confidence: 99%
“…Recently, AMPK has been shown to phosphorylate phosphodiesterase 4B, leading to its activation 149 , and this antagonizes glucagon-stimulated cAMP accumulation, an effect that would lead to decreased hepatic gluconeogenesis. Mice lacking liver AMPK also have lower levels of liver glycogen, which reduces glycogenic flux and blood glucose during exercise 146 . Similarly, during prolonged fasting, AMPK activation in muscle is important for promoting autophagy, muscle breakdown and the release of essential gluconeogenic precursors such as alanine 150 .…”
Section: [H1] Regulation Of Ampk Activitymentioning
confidence: 99%
“…Glucose derivatizations, GC-MS analysis, and MFA were completed using samples from 120 min before as well as 90, 100, and 110 min after the [ 13 C 3 ]propionate bolus, as outlined previously (46). Fragment ion ranges used for determining mass isotopomer distributions were as follows: aldonitrile, m/z 173-178, 259 -266, 284 -291, and 370 -379; methyloxime, m/z 145-149; di-O-isopropylidene, m/z 301-314.…”
Section: H/ 13 C Metabolic Flux Analysismentioning
confidence: 99%